2013
DOI: 10.1097/mlr.0b013e318286e32e
|View full text |Cite
|
Sign up to set email alerts
|

A Phased Cluster-randomized Trial of Rural Hospitals Testing a Quality Collaborative to Improve Heart Failure Care

Abstract: Significant improvements in 4 core measures were realized in stable environments (less nurse-turnover). Assuring appropriate nurse staffing and stability is essential to increase organizational preparation for quality initiatives and adoption of best practices in HF care in rural hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Patient‐centeredness means putting patients' interests first and considers patients' needs, expectations, and preferences to ensure that the delivery of care is based on these needs . Nurses were asked to grade on a 5‐point Likert scale the 5 dimensions designed by Planetree and Picker Institutes to measure the degree of patient‐centeredness: “patient‐centered continuity of care; patient‐centered communication and education; patient‐centered documentation and access to information; family involvement in patient care; and personalization of care.” Planetree and Picker Institutes adapted the questionnaire developed by the Agency for Healthcare Research and Quality to assess Consumer Assessment of Healthcare Providers and Systems, an internationally validated instrument for hospital survey . Thus, the self‐assessment tool of Planetree and Picker Institutes for measuring the degree of patient‐centeredness is considered in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient‐centeredness means putting patients' interests first and considers patients' needs, expectations, and preferences to ensure that the delivery of care is based on these needs . Nurses were asked to grade on a 5‐point Likert scale the 5 dimensions designed by Planetree and Picker Institutes to measure the degree of patient‐centeredness: “patient‐centered continuity of care; patient‐centered communication and education; patient‐centered documentation and access to information; family involvement in patient care; and personalization of care.” Planetree and Picker Institutes adapted the questionnaire developed by the Agency for Healthcare Research and Quality to assess Consumer Assessment of Healthcare Providers and Systems, an internationally validated instrument for hospital survey . Thus, the self‐assessment tool of Planetree and Picker Institutes for measuring the degree of patient‐centeredness is considered in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The staffing level of hospital nurses has a mixed effect on the outcome of care . Some studies have found that adequate staffing positively affects the QC and PS . Others have found that adequate staffing significantly affects quality outcomes, but not patient outcome .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the multilevel longitudinal hospital practice environment on patient outcome study Rural hospitals represent forty-one percent of nonfederal, shortterm general and specialty hospitals, and provided care for nineteen percent of all discharges nationally in 2006 [8]. Patient populations are older with poor or fair health, more likely to be uninsured, and are more remote from health care services.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention study is a randomized, controlled trial with two cohorts: intervention group and control groups. The intervention includes twoday onsite HF collaborative training by 1) access to experts through shared practice strategies and benchmark 2) HF tool kit; 3) monthly conference calls (8). Two survey's data were collected after intervention for measuring the hospital quality and organizational context, which includes practice environment scale (PES) measures and smoking cessation counseling scale (SCC) measures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation